Comparison of the risks of occupational diseases, avoidable hospitalization, and all-cause deaths between firefighters and non-firefighters: A cohort study using national health insurance claims data - Lee, Woo-Ri; Lee, Haejong; Nam, Eun Woo; Noh, Jin-Won; Yoon, Jin-Ha; Yoo, Ki-Bong (Frontiers in Public Health, 2023)
Objectives National Health Insurance claims data were used to compare the incidence of occupational diseases, avoidable hospitalization, and all-cause death standardized incidence ratio and hazard ratio between firefighters and non-firefighters. Methods The observation period of the study was from 2006 to 2015 and a control group (general workers and national and regional government officers/public educational officers) and a firefighter group was established. The dependent variables were occupational diseases, avoidable hospitalization (AH), and all-cause death. The analysis was conducted in three stages. First, the standardized incidence ratios were calculated using the indirect standardization method to compare the prevalence of the disease between the groups (firefighter and non-firefighter groups). Second, propensity score matching was performed for each disease in the control group. Third, the Cox proportional hazards model was applied by matching the participants. Results The standardized incidence ratio and Cox regression analyses revealed higher rates of noise-induced hearing loss, ischemic heart disease, asthma, chronic obstructive pulmonary disease, cancer, back pain, admission due to injury, mental illness, depression, and AH for firefighters than general workers. Similarly, the rates of noise-induced hearing loss, ischemic heart disease, asthma, chronic obstructive pulmonary disease, back pain, admission due to injury, mental illness, depression, and AH were higher in the firefighter group than in the national and regional government officer/public educational officer group. Conclusions The standardized incidence ratios and hazard ratios for most diseases were high for firefighters. Therefore, besides the prevention and management of diseases from a preventive medical perspective, management programs, including social support and social prescriptions in the health aspect, are needed.